The plasma polymerisation process for the deposition of amino-containing film on the poly(ethylene terephthalate) dressing-layer for safe wound-healing - Peršin, Zdenka (Materiali in tehnologije, 2012)
This article presents a new approach for preparing antimicrobial layer as a part of multi-composite dressing for safe and efficient wound - healing within a moist environment. Plasma polymerisation using a mixture of argon, ammonia, and hexane gases was used for preparing a thin polymer film on the poly(ethylene terephthalate) (PET) surface. The plasma deposition efficiency, regarding the amount of nitrogen, was evaluated by the Kjeldahl method, whilst the absorption of C.I. Acid Orange 7 dye onto accessible amino groups was monitored within the UV/VIS spectral region. The quantitative amount of charged surface groups was determined by potencometric titration. The results obtained using Kjeldahl method indicated the presence of a substantial amount of nitrogen within the deposited film. Furthermore, mono - azo acidic dye was absorbed onto the polymerised sample, pointing to the formation of an ionic bond between the sulphuric and amino groups. The plasma deposited PET samples resulted in inhibitions regarding all the pathogen microorganisms used, mostly those present in the infected wound.
Keywords: plazemska polimerizacija; argon; amoniak; plasma polymerisation; heksan; ammonia; polietilen tereftalat; protimikrobne lastnosti; hexane; obloga; polyethylene terephthalate; antimicrobial properties; wound dressing